2011
DOI: 10.1007/s00253-011-3814-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of sialylation on humanized IgG-like bispecific antibody by overexpression of α2,6-sialyltransferase derived from Chinese hamster ovary cells

Abstract: Improvement of glycosylation is one of the most important topics in the industrial production of therapeutic antibodies. We have focused on terminal sialylation with alpha-2,6 linkage, which is crucial for anti-inflammatory activity. In the present study, we have successfully cloned cDNA of beta-galactosyl alpha-2,6 sialyltransferase (ST6Gal I) derived from Chinese hamster ovary (CHO) cells regardless of reports that stated this was not endogenously expressed in CHO cells. After expressing cloned ST6Gal I in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 61 publications
(74 reference statements)
1
26
0
Order By: Relevance
“…Recently, new type of complicated artificial antibody with the Fc portion (i.e., compared to the expression level in the original host cell line at 72 h. Error bars represent the standard error of the mean (n = 3; single determination from each of three independent culture samples). **P \ 0.001, two sided unpaired t test single-chain diabody Fc) has been attractive molecules as new therapeutic reagents (Asano et al 2008;Onitsuka et al 2012). It is estimated that the assembly process is rate-limiting step for these complicated artificial antibody production in CHO cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, new type of complicated artificial antibody with the Fc portion (i.e., compared to the expression level in the original host cell line at 72 h. Error bars represent the standard error of the mean (n = 3; single determination from each of three independent culture samples). **P \ 0.001, two sided unpaired t test single-chain diabody Fc) has been attractive molecules as new therapeutic reagents (Asano et al 2008;Onitsuka et al 2012). It is estimated that the assembly process is rate-limiting step for these complicated artificial antibody production in CHO cells.…”
Section: Resultsmentioning
confidence: 99%
“…Also, non-natural Mab glycan structures (like sialylated triantennary glycans) may reduce their biological activity or even render them immunogenic. In a recent study, the CHO ST6Gal-I gene, present but not expressed, was cloned and stably expressed in these cells [45]. As a result, 70% of the glycans of a stably expressed IgG1 and released by PNGaseF were sialylated.…”
Section: Discussionmentioning
confidence: 99%
“…Onitsuka et al reported the development of a stable CHO cell line overexpressing the CHO ST6 (called ST6M). 46 They showed high sialylation level of the Fc portion of a human IgG1-based diabody, with »44% of disialylated diantennary glycans (G2S2, G2FS2), and »26% of G2FS1. Strikingly, while diabody Fc galactosylation in the parental cell line was relatively low (15% of digalactosylated G2F glycan), this level was highly enhanced in the ST6M cell line (76% of digalactosylated glycans overall; 6% as G2F and 70% as sialylated digalactosylated species).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the untranslated ST6 gene present in the CHO genome was cloned and reinserted, providing a functional ST6, which led to a good enhancement of IgG's sialylation, but the growth and viability of the CHO cells expressing ST6 were significantly affected. 46 Finally, it was shown that the co-expression of a rat ST6 with a mutant F243A IgG3 did not increase the overall Fc sialylation level, but rather resulted in a a2,6:a2,3 sialic acid ratio of 0.9:1. 33 Interestingly, this work also showed that the a2,3-sialylated F243A mutant had no affinity for FcgRI, FcgRII, and C1q, while the same mutant containing 50% of a2,6SA residues showed affinity for these receptors similar to that of the wild-type IgG3, highlighting the importance of properly determining the type of sialic acid linkage.…”
Section: Introductionmentioning
confidence: 99%